KELEMBAGAAN PEMASARAN TERNAK SAPI POTONG DI TIMOR BARAT, NUSA TENGGARA TIMUR - Yusuf ;; J. Nulik (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2008)
Cattle Marketing Institutions in West Timor, East Nusa Tenggara. The cattle marketing in East Nusa Tenggara (NTT) has not yet been conducted through a careful planning, but it is more influenced by cash needs. Besides that there were so many marketing channels before reaching the end consumers, thus the margins received were relatively variable. The aims of this research, were: (1) to find out the marketing channels of beef, (2) to find out the margin of each channel, (3) to find out various problems faced in beef marketing, and (4) to formulate recommended policies for the local government related to beef cattle development. Trader samplings were conducted by purposive samplings, i.e. by following the market channels, i.e. from: producers, village traders, livestock market traders, to the inter island traders (end consumers). Data collected in the research consisted of primary and secondary data. The results indicate that there are three market channels, i.e.: (1) Producers- village traders — livestock market traders — inter island traders, (2) Producers — livestock market traders — inter island traders, and (3) Producers — inter island traders. The highest marketing margin was obtained from the first marketing channel (Rp.1,062,500,- per head) and the lowest was from the third marketing channel (Rp.637,500,- per head). The main problem in the cattle marketing in NTT was the high cost of marketing caused by the execution of the local government regulations related to taxes, retributions and many other cost components that are difficult to avoid during the marketing process. Therefore there should be deregulation by the local government in relation to the provision of infrastructures and supporting facilities for marketing and the control on double tax payments, though they may have legal supports. Key words: Marketing, beef cattle, East Nusa Tenggara Pemasaran ternak sapi potong di NTT belum dilakukan dengan perencanaan yang matang, tetapi lebih dipengaruhi oleh adanya kebutuhan uang tunai. Selain itu masih banyaknya saluran pemasaran sampai ke konsumen akhir sehingga margin yang diterima petani relatif bervariasi. Tujuan penelitian: (1) mengetahui saluran pemasaran temak potong, (2) mengetahui margin dari setiap saluran pemasaran, (3) mengetahui berbagai masalah yang dihadapi dalam pemasaran temak potong, dan (4) merumuskan rekomendasi kebijakan kepada Pemda berkaitan dengan pengembangan ternak potong. Pengambilan sampel pedagang dilakukan secara purposive sampling, yaitu dengan mengikuti saluran pemasaran yang dilalui oleh temak sapi, yakni dari Produsen, Blantik Desa, Blantik Pasar Hewan sampai ke Pedagang Antar Pulau (konsumen akhir). Data yang dikumpulkan dalam penelitian ini meliputi data primer dan data sekunder. Hasil penelitian menunjukkan terdapat tiga bentuk saluran pemasaran, yaitu : (1) Produsen - blantik desa - blantik pasar hewan - pedagang antar pulau, (2) Produsen - blantik pasar hewan - pedagang antar pulau, (3) Produsen - pedagang antar pulau. Margin pemasaran yang paling besar adalah pada saluran I yakni Rp.1.062.500/ekor dan yang terkecil pada saluran HI yakni Rp.637.500/ekor. Masalah utama dalam pemasaran ternak adalah tingginya biaya pemasaran akibat diperlakukannya berbagai Perda terkait dengan pajak, retribusi serta banyaknya komponen biaya pemasaran yang sulit dihindari selama proses pemasaran. Perlunya deregulasi Pemda terkait sarana dan prasarana pemasaran dan menertibkan pungutan—pungutan ganda sekalipun mempunyai kekuatan hukum. Kata kunci : Pemasaran, ternak potong, Nusa Tenggara Timur